PENGARUH MODEL PEMBELAJARAN ROUNDCONSEN TERHADAP KEMAMPUAN MENULIS TEKS TANGGAPAN - Nurul Lutfiah; Ratna Dewi Kartikasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing skills represent a crucial language competency, yet they are often perceived as the most challenging by students. This research is motivated by the low response text writing ability among seventh-grade students at SMP Negeri 3 Gunungsindur. This deficiency is influenced by several factors, including limited grammar and vocabulary mastery, difficulties in systematically formulating ideas, and the reliance on conventional, less innovative learning models. This study aims to analyze the implementation and actual influence of the Roundconsen cooperative learning model (an integration of the Roundtable and Concept Sentence models) on the response text writing skills of seventh-grade students The research applied a quantitative methodology with a true experimental design, specifically the Post-test Only Control Group Design. The research population encompassed all seventh-grade students at SMP Negeri 3 Gunungsindur distributed across nine classes (a total of 216 students). The sample was selected using simple random sampling, resulting in class VII.2 (34 students) as the experimental group taught using the Roundconsen learning model, and class VII.8 (34 students) as the control group taught using the conventional learning method. Data were gathered through a response text writing performance test (post-test) evaluated based on a standardized rubric (content relevance, structure, language use, spelling, and vocabulary) as well as supporting observation, interviews, and documentation. The data analysis techniques involved descriptive statistics and parametric tests (Kolmogorov-Smirnov normality test, Levene's homogeneity test, and Independent Samples T-test) conducted using SPSS version 25. The results of the study indicate a statistically significant difference in writing performance between the two groups. The experimental group achieved a post-test mean score of 83.79 (very good category), with scores ranging from 79 to 89. Conversely, the control group achieved a mean score of 71.88 (good category), with scores ranging from 65 to 78. Based on the Independent Samples T-Test, a significance value (2-tailed) of 0.000 was obtained, which is lower than the significance threshold of 0.05 (Sig. < 0.05). The hypothesis testing results indicate that the null hypothesis () is rejected and the alternative hypothesis () is accepted, confirming a positive and significant influence of the Roundconsen learning model on improving students' response text writing skills. This integrative approach is proven to foster active engagement, group cooperation, critical and creative thinking, and efficiency in constructing structured, grammatically appropriate response texts.